Application of Optical Spectrophotometry for Analysis of Radiation Spectrum Emitted by Electric Arc in the Air - Kozioł, Michał; Wotzka, Daria; Boczar, Tomasz; Frącz, Paweł (Journal of Spectroscopy, 2016)
This paper presents the results of measurement and analysis of optical radiation emitted by a free burning electric arc. The aim was to determine the application possibilities of optical spectrophotometry for detection of electric arcs. The research works considered electric arc generated with a constant voltage supply between two copper electrodes in the air, carried out under laboratory conditions. A high resolution optical spectrophotometer was used for registration of optical radiation. The analyses involved determination of two dimensionless descriptors obtained for the gathered spectra. Moreover, for each of the registered intensity distributions, the energy values were calculated for three frequency ranges. Based on the measured signals, the possibility of application of spectrophotometry for the optical radiation analysis was confirmed. The analysis indicated that the most energy of optical radiation is detected for the range of 200–780 nm, while above 780 nm almost no optical energy is emitted. Spectrophotometric studies performed in the UV-NIR range are of interest since one can obtain information about the structural defects (at lower wavebands) or impurities and/or point defects (at low energies bands). It was also stated that the obtained descriptors may be applied for diagnosis and identification of electric arc purposes.